The Temporal Stability of Buyers’ Preferences for Property Localization on the Housing Market in Szczecin - Batóg, Barbara; Foryś, Iwona (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The housing market investors’ decisions are caused by their subjective expectations. These decisions are to do with financial resources, activity of local developers and buyers’ individual needs connected to the size of their household or their specific habits, as well as a sense of security and prestige of the neighborhood. The localization of a property is one of the most significant determinants of its price because of its spatial constancy. The attributes of a given residential area influence the value of properties and this phenomenon can be observed through intensity of transactions and transaction prices. On the other hand, the neighborhood’s influence changes over time. These changes are sometimes slow but could be very substantial. That is why buyers’ preferences can also change over time. The aim of this research is the analysis of the temporal stability of buyers’ localization preferences on the housing market in Szczecin. The fixed effects model, which allows for the comparison of changes in apartments’ prices in residential areas, has been applied. The data came from notarial deeds, from registers of real estate prices and values concerning transactions on the housing market in Szczecin.